2011
DOI: 10.1111/j.1467-789x.2010.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary weight loss: systematic review of early phase body composition changes

Abstract: SummaryWeight loss follows when adult humans enter a phase of negative energy balance brought about by reducing energy intake and/or increasing energy expenditure. The weight loss period is usually viewed as a continuous process, ending when energy equilibrium is achieved at a lower weight or with death following depletion of fuel stores. However, growing evidence supports the expanded view that induction of negative energy balance leads to well-defined physiological effects characterized by three discrete pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
119
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 57 publications
5
119
1
7
Order By: Relevance
“…In particular, each gram of protein in the organ mass was accompanied by 1.6–3.35 g of water and therefore contributed to daily changes in FFM (Heymsfield et al. 2011). It is important to note that FFM is composed of approximately 70–75% of total body water, that is, the hydration factor (Wang et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, each gram of protein in the organ mass was accompanied by 1.6–3.35 g of water and therefore contributed to daily changes in FFM (Heymsfield et al. 2011). It is important to note that FFM is composed of approximately 70–75% of total body water, that is, the hydration factor (Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Geddes and colleagues in their early studies analyzed liver glycogen molecule size in vitro and showed that the each gram of glycogen had 1.5–2.7 g of water attached to it (Heymsfield et al. 2011). Similarly, each gram of glycogen is stored in human muscle with 3 grams of water (Fernandez‐Elias et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A adoção de dietas saudáveis pode ter relação com a prática de atividade física, visto haver relação entre estado nutricional e atividade física vinculada à execução de tarefas da vida diária e de práticas de caminhadas, esporte e lazer ativo 12,13 .…”
unclassified